1975
DOI: 10.2172/4178286
|View full text |Cite
|
Sign up to set email alerts
|

Design of a force-free inductive storage coil

Abstract: Force-free coils have been considered for various applications as energy storage devices. A novel energy storage system consisting of both toroidal and poloidal coils has been developed. In this system, the Lorentz forces on the two coils are in opposition and can be made to cancel by having the proper ratio of ampere-turns in the two coils. A general discussion of force-free coil design is given,and the toroidal-poloidal coil system is described. The materials costs of magnets constructed with this and other … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1980
1980
2003
2003

Publication Types

Select...
2
2
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…One of these configurations, shown in Figure 10, has been proposed by Mawardi (1975). In this configuration the poloidal and toroidal components have been decomposed by setting a coil carrying a poloidal current inside a toroidal shell which supports coils carrying a toroidal current.…”
Section: Several Force-free Configurations Have Already Been Studiedmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these configurations, shown in Figure 10, has been proposed by Mawardi (1975). In this configuration the poloidal and toroidal components have been decomposed by setting a coil carrying a poloidal current inside a toroidal shell which supports coils carrying a toroidal current.…”
Section: Several Force-free Configurations Have Already Been Studiedmentioning
confidence: 99%
“…Coi! carrying poloidalcurrent Thome, 1982) " Mawardi (1975) analysis revealed that no significant gains are made at low energy storage, but beyond I M J, substantial gains (40%) could be achieved with force-free coils.…”
Section: Coilscorrying Foeoidal Currentmentioning
confidence: 99%
See 1 more Smart Citation